Public Policies to Access to Digital Technologies in the Brazilian Educational Context (Research, Society and Development, 2022)
In this study, we will present five projects and programs implemented under the aegis of the universalization of broadband expansion in Brazil. Considering that access to the internet for public school students is intrinsically related to projects for the use of other TDICs, we will point out how National Broadband Expansion Projects have unfolded in recent years, identifying the differences between their implementation in the South and the north of the country. We will evaluate the objectives of projects to insert TDICs in the educational context to answer the following question: How are policies for universal access to TDICs being implemented in the Brazilian educational context? The time frame will be 1997 to 2021. The research will have documentary character with a Foucauldian discursive analysis. The data showed that broadband internet expansion policies in Brazil suffered a significant interruption between the years 2016 and 2020 and that the most affected by this were the North Region, where most of the Brazilian Amazon is concentrated.